Terazosin therapy for patients with female lower urinary tract symptoms: a randomized, double-blind, placebo controlled trial. - Low, B; Liong, M; Yuen, K; Chee, C; Leong, W; Chong, W; Khan, N; Cheah, P; Liong, K (2008)
PURPOSE: We determined the clinical efficacy and safety of terazosin in the treatment of patients with female lower urinary tract symptoms. MATERIALS AND METHODS: A total of 100 females 20 to 70 years old who met the inclusion criteria of total International Prostate Symptom Score 8 or greater, symptom duration 1 or more months, and did not meet any exclusion criteria were entered into the study. Subjects were randomized to receive terazosin or placebo in titrated dose from 1 mg od, 1 mg twice daily to 2 mg twice daily during 14 weeks. Successful treatment outcomes use primary end point of International Prostate Symptom Score quality of life 2 or less and secondary end point of total International Prostate Symptom Score 7 or less. Other outcome measures included International Prostate Symptom Score individual item scores, King's Health Questionnaire quality of life domains, objective assessment parameters of 24-hour frequency volume chart, maximum flow rate and post-void residual urine. RESULTS: Using a primary end point, 32 of 40 (80%) evaluable terazosin subjects responded in contrast to 22 of 40 (55%) evaluable placebo subjects (p <0.02). The secondary end point revealed a successful outcome in 85% of terazosin subjects vs 55% in placebo (p <0.01). Of the 7 International Prostate Symptom Score individual item scores, only item scores of frequency and straining showed statistically significant reductions with terazosin (p <0.01). All King's Health Questionnaire quality of life domains except domain of severity measures showed statistically significant improvement with terazosin (p <0.05). There were no differences between treatment groups in all objective assessment parameters. Of all evaluable subjects 23 of 40 (58%) on placebo experienced adverse events vs 16 of 40 (40%) on terazosin (p >0.05). CONCLUSIONS: Terazosin proved to be more effective and safe than placebo in patients with female lower urinary tract symptoms.